2006
DOI: 10.1038/nprot.2006.71
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of mouse embryonic stem cells to insulin-producing cells

Abstract: Here, we describe a basic protocol for the in vitro differentiation of mouse embryonic stem (ES) cells into insulin-producing cells. The three-step protocol comprises (i) the formation of embryoid bodies, (ii) the spontaneous differentiation of embryoid bodies into progenitor cells of ecto-, meso- and endodermal lineages, and (iii) the induction of differentiation of early progenitors into the pancreatic lineage. Differentiated cells can be obtained within approximately 33 d. Differentiation induction by growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 37 publications
2
93
0
Order By: Relevance
“…For immunolabelling see [40] and [8]. Bar=50 μm (a), 20 μm (b-g) produced during neuronal [18] and pancreatic [1,[7][8][9]19] differentiation of ES cells, respectively (see [19][20][21][22]). …”
Section: Neuronal Vs Pancreatic Differentiation In Vivo and Of Es Celmentioning
confidence: 99%
See 1 more Smart Citation
“…For immunolabelling see [40] and [8]. Bar=50 μm (a), 20 μm (b-g) produced during neuronal [18] and pancreatic [1,[7][8][9]19] differentiation of ES cells, respectively (see [19][20][21][22]). …”
Section: Neuronal Vs Pancreatic Differentiation In Vivo and Of Es Celmentioning
confidence: 99%
“…Instead, using the same differentiation protocol, it was found that insulin immunoreactivity occurred as a consequence of insulin uptake from the medium [2], neuronal cells were formed [2][3][4], or insulin was released as an artefact from differentiated ES cells [2,3]. Functional pancreatic cells, however, were successfully generated using lineage selection strategies based on pancreas-specific promoters [5,6], by modified protocols in combination with transgene expression [7][8][9], or by addition of a phosphoinositol-3 kinase inhibitor [10]. The differentiated cells showed properties of (neonatal) beta cells, such as insulin transcripts and C-peptide/insulin co-expression, insulin-secretory granules, ion channel activity of embryonal beta cells, and normalisation of blood glucose level after transplantation into diabetic mice [5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…For RNA isolation, yeast cells were suspended in lysis buffer (4 M guanidinium thiocyanate, 25 mM sodium citrate, pH 7, 0.5% sodium N -lauroylsarcosinate, 1% mercaptoethanol). The isolation of total RNA was carried out according to Schroeder et al (2006). cDNA was synthesized following the recommendations provided in the instruction manual First Strand cDNA Synthesis (Fermentas, Germany).…”
Section: E Böer Et Almentioning
confidence: 99%
“…Although the amount of insulin produced by these clusters was not sufficient to correct hyperglycemia, the implanted cells did impart a survival and health benefit to its recipient. Schroeder et al [99] generated C-peptide/ insulin-positive islet-like clusters that release insulin upon glucose stimulation through a three step culture process; these clusters were also able to induce the normalization of glycemia in STZ-diabetic mice.…”
Section: Embryonic Stem Cellsmentioning
confidence: 99%